Quantification of the zymogenicity and the substrate-induced activity enhancement of complement factor D - Dani, Ráhel; Oroszlán, Gábor; Martinusz, Róbert; Farkas, Bence; Dobos, Bernadett; Vadas, Evelin; Závodszky, Péter; Gál, Péter; Dobó, József (Frontiers in Immunology, 2023)
Complement factor D (FD) is a serine protease present predominantly in the active form in circulation. It is synthesized as a zymogen (pro-FD), but it is continuously converted to FD by circulating active MASP-3. FD is a unique, self-inhibited protease. It has an extremely low activity toward free factor B (FB), while it is a highly efficient enzyme toward FB complexed with C3b (C3bB). Structural basis of this phenomenon is known, however the rate enhancement was not yet quantified. It has also been unknown whether pro-FD has any enzymatic activity. In this study, we aimed to measure the activity of human FD and pro-FD toward uncomplexed FB and C3bB in order to quantitatively characterize the substrate-induced activity enhancement and zymogenicity of FD. Pro-FD was stabilized in the proenzyme form by replacing Arg25 (precursor numbering) to Gln (pro-FD-R/Q). Activated MASP-1 and MASP-3 catalytic fragments were also included in the study for comparison. We found that complex formation with C3b enhanced the cleavage rate of FB by FD about 20 million-fold. C3bB was also a better substrate for MASP-1, about 100-fold, than free FB, showing that binding to C3b renders the scissile Arg-Lys bond in FB to become more accessible for proteolysis. Though easily measurable, this cleavage by MASP-1 is not relevant physiologically. Our approach provides quantitative data for the two-step mechanism characterized by the enhanced susceptibility of FB for cleavage upon complex formation with C3b, and the substrate-induced activity enhancement of FD upon its binding to C3bB. Earlier MASP-3 was also implicated as a potential FB activator, however, MASP-3 does not cleave C3bB (or FB) at an appreciable rate. Finally, pro-FD cleaves C3bB at a rate that could be physiologically significant. The zymogenicity of FD is about 800, i.e. the cleavage rate of C3bB by pro-FD-R/Q was found to be about 800-fold lower than that by FD. Moreover, pro-FD-R/Q at about 50-fold of the physiological FD concentration could restore half maximal AP activity of FD-depleted human serum on zymosan. The observed zymogen activity of pro-FD might be relevant in MASP-3 deficiency cases, or during therapeutic MASP-3 inhibition.